Pengaruh Ukuran Perusahaan dan Manajemen Laba terhadap Agresivitas Pajak - Karlina, Lilis; Rahmasari, Intan; Winingrum W.A, Sri Putri (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2024)
The objective of this quantitative study is to examine the relationship between earnings management, company size, and tax aggressiveness. The analysis is limited to non-cyclical consumer companies that were publicly traded on the Indonesia Stock Exchange between 2017 and 2021. A purposive sampling technique was applied to obtain a representative sample of 26 companies. The analysis of secondary data obtained from annual financial reports involved the application of panel data regression. This approach involved conducting descriptive statistical analysis, hypothesis testing, classical assumption tests, and selection of regression models. The results suggest that although there is a partially negative relationship between company size and tax aggressiveness, there is no statistically significant effect of earnings management. Nevertheless, when taken into account in tandem, earnings management and company size have a significant impact on tax aggressiveness.